The interlibrary loan services of the University Of Malaya Library - Norehan, A. (University of Malaya Library, 1986)
Describes the Inter-library loan services at the University of malaya Library. Records of requests for 10 years were investigated. Also include information about methods of requesting, materials being borrowed, problems faced when processing requests and modification of the inter-library loans conditions as a result of service abuse.